2014
DOI: 10.1016/j.jiph.2014.01.006
|View full text |Cite
|
Sign up to set email alerts
|

Group B streptococcal infective endocarditis

Abstract: Streptococcus agalactiae (S. agalactiae), also referred as group B streptococcus (GBS), is an important pathogen in neonates and a rare cause of invasive infection in adults. It is well known that GBS endocarditis is a virulent infection that can cause serious complications. The overall mortality rate remains high despite surgical treatment. We describe a case of native mitral valve endocarditis caused by GBS in an 86-year-old woman treated medically.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
1

Year Published

2017
2017
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 10 publications
0
9
0
1
Order By: Relevance
“…Streptococcus agalactiae causa meningitis, neumonía y sepsis en neonatos con alta morbilidad y mortalidad, siendo responsable de las infecciones más graves que puede presentar un individuo en sus primeras horas de vida (2) . Se asocia también a infecciones urinarias, infecciones de heridas quirúrgicas post-cesárea, sepsis puerperal y actualmente en pacientes con enfermedades crónicas subyacentes, relacionado a infecciones invasivas severas, como neumonía, peritonitis, endocarditis, meningitis, osteomielitis, artritis, celulitis necrotizante y fascitis necrotizante (2,3,4) . La infección perinatal causada por SGB puede ser de inicio precoz, dentro de los primeros 6 días de vida comenzando generalmente dentro de las 12 horas del nacimiento o, de inicio tardío, luego de la primera semana de vida y hasta los tres meses.…”
Section: Introductionunclassified
“…Streptococcus agalactiae causa meningitis, neumonía y sepsis en neonatos con alta morbilidad y mortalidad, siendo responsable de las infecciones más graves que puede presentar un individuo en sus primeras horas de vida (2) . Se asocia también a infecciones urinarias, infecciones de heridas quirúrgicas post-cesárea, sepsis puerperal y actualmente en pacientes con enfermedades crónicas subyacentes, relacionado a infecciones invasivas severas, como neumonía, peritonitis, endocarditis, meningitis, osteomielitis, artritis, celulitis necrotizante y fascitis necrotizante (2,3,4) . La infección perinatal causada por SGB puede ser de inicio precoz, dentro de los primeros 6 días de vida comenzando generalmente dentro de las 12 horas del nacimiento o, de inicio tardío, luego de la primera semana de vida y hasta los tres meses.…”
Section: Introductionunclassified
“…The most common clinical presentations of S. agalactiae infection in non-pregnant patients include bacteremia without a focus and soft tissue infection. Less commonly, it causes endocarditis, urinary tract infection, and abdominal infections [ 3 - 6 ]. The risk factors for developing invasive S. agalactiae infections include chronic kidney disease, cardiac failure, history of neoplasia, history of ischemic heart disease, and diabetes mellitus [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…The risk factors for developing invasive S. agalactiae infections include chronic kidney disease, cardiac failure, history of neoplasia, history of ischemic heart disease, and diabetes mellitus [ 5 ]. S. agalactiae endocarditis is an aggressive disease with a significant rate of local and systemic complications [ 6 ]. Complications associated with infection by S. agalactiae include embolization, heart failure, and significant mortality [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…4 Previous authors have reported group B streptococcal endocarditis as a complication of elective abortion. [5][6][7][8][9] In the current case, the patient underwent elective surgical abortion with retained products of conception. Her initial febrile presentation may have been the result of clinically unapparent intrauterine infection, with or without bacteremia, that was partially treated with orally administered amoxicillin.…”
Section: Group B Streptococcal Endocarditismentioning
confidence: 91%
“…Most available research on group B streptococcal endocarditis is limited to case reports and case series. 2,[5][6][7][8][9] Crespo and colleagues 5 reviewed 11 obstetrical-and gynecological-related cases of group B streptococcal endocarditis from 1985 to 2003. The majority of women (64%) had no predisposing valvular lesions, and 5 cases (45%) followed therapeutic abortion.…”
Section: Group B Streptococcal Endocarditismentioning
confidence: 99%